علاج جسؤ القضيب الليفي (داء بيروني) - حرفوش, أيمن (Latakia University Journal -Medical Sciences Series, 2019)
في مشفى الأسد الجامعي باللاذقية والفترة بين عامين 1996-2006م تمت معالجة 34 مريضاً مصاباً بجسؤ القضيب الليفي, خضع جميع المرضى لمعالجة محافظة بفيتامين E بمعدل 1000 وحدة دولية يومياً لمدة ثلاثة أشهر. كما عولج 19 مريضاً مصاباً بإنعطاف شديد في القضيب يعيق الممارسة الجنسية معالجة جراحية, وذلك بطريقة Nesbit . المعالجة المحافظة أدت إلى زوال الألم عند 9 مرضى (26.47 %), بينما لم يطرأ اي تطور يذكر على الأعراض السريرية الأخرى. نتائج المعالجة الجراحية كانت جيدة إذ أدت العملية الجراحية إلى تصحيح الإنعطاف في القضيب عند 16 مريضاً 84.21% من أصل 19 مريضاً, كما تم زوال الألم في القضيب عند 8 مرضى 42.1% من أصل 19 مريضاً. A treatment has been achieved in 34 patients with induratio penis were treated at AL–Assad University Hospital between 1996 – 2006. All patients were involved in a conservative treatment by using 1000 international units of E – Vitamine per day for 3 months. 19 patients with great bending in penis were involved in surgical treatment by the means of Nesbit. The conservative treatment causes the disappearance of pain with 9 patients (26.47%), while there was no improvement that could be mentioned with regard to other clinical symptoms. The results of the surgical treatment were good. The surgery corrected the inclination in the penis in 16 patients 84.21% out of 19 patients. The pain also diapered in penis in 8 patients 42.1% out of 19 patients.